Multiple Intelligences in Evaluation of Arabic Learning at Islamic Boarding School - Ridlo, Ubaid (Arabiyatuna: Jurnal Bahasa Arab, 2022)
The purpose of this study was to find a variation of test technique and variety of test in Arabic Language-Tamrinul Lughah subject and analyze it based on the theory of multiple intelligences at Darul Muttaqien Islamic Boarding School Bogor West Java. This research is field research conducted at Tarbiyatul Mu’allimin wal Mu’allimat al-Islamiyyah (TMI) class II since July 2018 up to August 2020. This research is qualitative, using case study method. Methods of data collection through interview, observation, focus group discussion, and documentation. The steps of data analysis are carried out qualitatively. By stages; 1) data collection, 2) data reduction, 3) display data with analysis, 4). conclusion. The findings of this study are Pesantren in implementing Arabic learning evaluation-Tamrinul Lughah have applied the Non-Test and Test Techniques. While the variety of tests includes Akhlak Mulya Test, Kepribadian Test, Formative Test, Summative Middle Test, and Summative Final Test both written and oral. The variety of tests has proven to be able to develop santri’s multi-intelligence, including linguistic intelligence, spiritual intelligence, interpersonal intelligence, and intrapersonal intelligence. So, the evaluation of learning Arabic based on multiple intelligences is very effective in improving student achievement.